THE CONCEPTUAL PAIR OF “KNOWLEDGEABILITY” AND “IGNORANCE” (KONFERENSIYA, 2025)
This article examines the conceptual domains ofknowledgeability and ignorance, exploring the linguistic units that representthese notions, their role and significance in human life, and their spiritualfoundations. The study argues that language functions not only as a tool forexpressing this pair of opposing concepts but also as an important means ofshaping their social, cultural, and personal significance.